LEVELS OF POLITENESS IN INTERACTIONS BETWEEN TRADERS AND VISITORS IN PANTAI MATRAS - Afandi, Rizky Arif; Robing, Robing (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
In Bangkanese society, politeness is a crucial social component measured by how individuals treat one another in social situations. Here, being polite is understood to include having decent manners, which include saying hello, recognising, and thanking people. This study looks at the interactions between traders and tourists in Pantai Matras, taking its inspiration from the Bangka government, which places a strong emphasis on manners. The utilisation of openings and closings in 20 transactions that were retrieved over a week through attentive monitoring was the main focus of the study. The data were then transcribed. The Bangkanese concept of good manners, which includes greeting and thanks, and Brown and Levinson's (1987) idea of politeness in illocutionary acts were employed as a framework. According to our data, the traders in Pantai Matras used more semi-polite beginnings but more polite closings to wrap up their deals. A more thorough examination of the data shows that this politeness was frequently offered in reaction to the visitor's requests. Even though our results are not as significant as others, we think they will be helpful to researchers and practitioners because they show that professional communication skills must be taught and used when having transactions in Pantai Matras.